Total synthesis of human beta-lipotropin. - Blake, J (1983)
The total synthesis of human beta-lipotropin has been accomplished by the new segment-coupling method in aqueous solution. The peptides Ac-Arg-beta-lipotropin-(61-89) (I) and [GlyS60]-beta-lipotropin-(1-60) (II) were synthesized by the solid-phase method. Reaction of peptide I with citraconic anhydride followed by brief digestion with trypsin to remove the acetylarginyl group, gave Ia. Reaction of peptide II with citraconic anhydride gave the citraconyl peptide IIa. Ia and IIa were coupled together in 50% dimethylformamide by reaction with silver nitrate/N-hydroxysuccinimide. After removal of the citraconyl groups in 25% acetic acid, a 10% yield of synthetic beta-lipotropin could be isolated. The synthetic product was shown to be identical to native human beta-lipotropin by paper electrophoresis, isoelectric focusing, HPLC, lipolytic activity in isolated rabbit fat cells, and radioimmunoassay.